Non-coding RNAs mediate mechanical load-regulating bone metabolic homeostasis - Huang, Ruiqi; Chang, Bo; Yi, Xuejie (Frontiers in Cell and Developmental Biology, 2025)
Bone, as a highly active organ, relies on dynamic mechanical stimulation for its continuous remodeling and regeneration. Mechanotransduction, the regulatory process through which mechanical forces are converted into biochemical signals, involves intricate interactions within and between cells and their extracellular environment, playing a crucial role in maintaining bone metabolic homeostasis. The complexity of this process stems primarily from the diversity of input signals and the precise regulation of downstream signaling cascades. In recent years, studies have revealed that non-coding RNAs (ncRNAs) play a key role in mediating the regulation of bone metabolism by mechanical loading. This review elaborates on how mechanosensitive ncRNAs participate in the regulation of bone mechanotransduction signaling pathways. Furthermore, we explore how different mechanical stimuli (such as loading and unloading) influence skeletal adaptive responses by modulating the expression of ncRNAs. Thus, this article not only provides novel perspectives on the mechanical regulatory functions of ncRNAs in bone metabolism, but also offers new strategies for preventing and treating bone metabolic disorders caused by mechanical disuse.